Protection of mental healthcare documents using sensitivity-based encryption. (15th March 2021) - Rangaraj, Kalaiselvi; Veerasamy, Vanitha; Sumathi, V.P.
As all the domains move towards digitisation, maintaining voluminous digital data becomes a vital issue in organisations and enterprises. Especially ensuring data security and privacy is the most important problem. In the domains such as healthcare, data security breaches and patient identity theft are the growing concerns in current scenario. Adopting IT services which are provided under cloud-based technologies again increases the security threats in healthcare data maintenance. Cloud-based technologies also ensures data security to a certain level by employing cryptographic techniques though several cryptographic techniques exist to protect data, the selection of appropriate technique increases the security while reducing the processing cost. Cryptographic techniques can be chosen based on the content of the digital document involved in various applications. The proposed method analyses the sensitive terms involved in textual medical documents and determines the adoption of appropriate cryptographic techniques. As security remains top concern for cloud adoption the proposed sensitivity-based encryption improves the security and encryption efficiency at a significant level. The experimentation reveals that about 4% of time complexity gets reduced in encryption.